101 top tips for DSLR video - Juniper, Adam.; Newton, David (Lewes. : Ilex, 2011)
The new generation of dSLR cameras include high-definition (HD) video, and this is opening up a whole new realm of creative possibilities to photographers. Even if you're a novice, the tips and techniques in this practical guide will soon have you planning, shooting, and editing movies in HD, like the filmmaker you always thought you could be!
Includes index.
"Using your camera to make great movies"--Cover.
Keywords: High definition video recording; Digital cameras; Single-lens reflex cameras